2016
DOI: 10.1039/c6dt01801g
|View full text |Cite
|
Sign up to set email alerts
|

M2L4 coordination capsules with tunable anticancer activity upon guest encapsulation

Abstract: Metallosupramolecular cages and capsules have gained increasing popularity as both molecular containers and anticancer agents. For successful combination of these properties a thorough analysis of the effect of guest encapsulation on the host's cytotoxic properties is highly required. Here we report on the cytotoxicity modulation of Pt(ii) and Pd(ii)-linked M2L4 coordination capsules upon encapsulation of guest molecules such as pyrene and caffeine. The anticancer activity of the capsules against various human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 69 publications
0
45
0
Order By: Relevance
“…The quinoline cages C q and C iq were more cytotoxic than all the [Pd 2 ( L tripy ) 4 ] 4+ cage systems reported in the literature (IC 50 values for the L tripy based systems ranged from 10 to 100 μM) (McNeill et al, 2015 ; Kaiser et al, 2016 ; Schmidt et al, 2016b ). Additionally, C q was also more active, albeit against different cancer cell lines (HL-60, HL-60/Dox, HT-29, T-24, SKW-3), than the hydrophobic [Pd 2 ( L anthracene ) 4 ] 4+ cages of Yoshizawa and Ahmedova (IC 50 values ranged from 0.9 to 37.4 μM) (Ahmedova et al, 2016 ; Anife et al, 2016 ). C q was also more cytotoxic than a hydrophobic bis -hexyl-1,2,3-triazole substituted [Pd 2 ( L hextrz ) 4 ] 4+ helicate, C hextrz , we developed previously (IC 50 values = 6.9 and 6.0 μM against A549 and MDA-MB-231, respectively) (McNeill et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quinoline cages C q and C iq were more cytotoxic than all the [Pd 2 ( L tripy ) 4 ] 4+ cage systems reported in the literature (IC 50 values for the L tripy based systems ranged from 10 to 100 μM) (McNeill et al, 2015 ; Kaiser et al, 2016 ; Schmidt et al, 2016b ). Additionally, C q was also more active, albeit against different cancer cell lines (HL-60, HL-60/Dox, HT-29, T-24, SKW-3), than the hydrophobic [Pd 2 ( L anthracene ) 4 ] 4+ cages of Yoshizawa and Ahmedova (IC 50 values ranged from 0.9 to 37.4 μM) (Ahmedova et al, 2016 ; Anife et al, 2016 ). C q was also more cytotoxic than a hydrophobic bis -hexyl-1,2,3-triazole substituted [Pd 2 ( L hextrz ) 4 ] 4+ helicate, C hextrz , we developed previously (IC 50 values = 6.9 and 6.0 μM against A549 and MDA-MB-231, respectively) (McNeill et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they have measured the cytotoxicity of mixtures of the cages and cisplatin and unsurprisingly have found that those mixtures are more cytotoxic than cage alone (IC 50 = 2–13 μM). Yoshizawa, Ahmedova and co-workers have also found that [M 2 ( L ) 4 ] 4+ (M = Pd 2+ or Pt 2+ ) cages with similar, but more hydrophobic, dipyridyl anthracenyl ligands ( L anthracene ) display high anticancer activity (IC 50 values range from 0.9 to 37.4 μM against HL-60, HL-60/Dox, HT-29, T-24, SKW-3 cancer cell lines) (Ahmedova et al, 2016 ; Anife et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Yoshizawa reported two Pt II ‐ and Pd II ‐linked M 2 L 4 coordination capsules, exhibiting anticancer activities superior to cisplatin against two types of leukemic cells (HL‐60 and SKW‐3) and pronounced toxicity against cisplatin‐resistant cells (HL‐60/CDDP) (Figure ). Notably, the cytotoxic selectivity of the Pt II and Pd II capsules toward cancerous cells are up to 5.3‐fold higher than that of cisplatin.…”
Section: Anticancer Activitiesmentioning
confidence: 99%
“…Decomposition of the capsules can be easily monitored by the appearance of the characteristic strong fluorescence of the liberated bis-anthracene ligand L16 . Further on, the effect of guest encapsulation on the stability and the cytotoxicity of the capsules have been investigated (Ahmedova et al, 2016a). A successful modulation of these properties has been achieved by encapsulation of different types of hydrophobic guest molecules (pyrene and caffeine).…”
Section: Metallocapsules and Barrelsmentioning
confidence: 99%